2022
DOI: 10.1111/add.15783
|View full text |Cite
|
Sign up to set email alerts
|

Did the under‐reporting of meth/amphetamine use increase in a general population survey in Australia as negative media coverage increased?

Abstract: Aim To test (1) if there was a change in self‐reported lifetime prevalence of meth/amphetamine use by birth cohort and (2) if the extent of under‐reporting of meth/amphetamine use was associated with the proportion of the population who nominated meth/amphetamine as a drug problem. Design Observational study using seven waves of repeated cross‐sectional nationally representative household surveys between 2001 and 2019. Setting Australia. Participants Participants were from three birth cohorts: 1951–60 (age 68–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The disproportionate media attention may instead reflect increases in harms associated with methamphetamine use perhaps due to increase in the use of crystal (as opposed to less potent forms) methamphetamine, or a perception of increased harms given people who use crystal methamphetamine are more likely to present to hospital [20]. However, it should also be noted that it is difficult to accurately measure the prevalence of illicit drugs such as methamphetamine using population‐based surveys, and it has been suggested that the prevalence of methamphetamine use may be underreported in surveys due to stigma, discrimination and negative attitudes commonly associated with the drug [21].…”
Section: Discussionmentioning
confidence: 99%
“…The disproportionate media attention may instead reflect increases in harms associated with methamphetamine use perhaps due to increase in the use of crystal (as opposed to less potent forms) methamphetamine, or a perception of increased harms given people who use crystal methamphetamine are more likely to present to hospital [20]. However, it should also be noted that it is difficult to accurately measure the prevalence of illicit drugs such as methamphetamine using population‐based surveys, and it has been suggested that the prevalence of methamphetamine use may be underreported in surveys due to stigma, discrimination and negative attitudes commonly associated with the drug [21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in systematic reviews of harms among people who inject drugs, 602 studies have reported on HIV and 417 studies have reported on hepatitis B and C viruses [21], compared to only 23 studies on mental health indicators [22]. Further, the dearth of literature on methamphetamine and depression could be because studies often lack the sample size to investigate the topic, because methamphetamine use is highly stigmatised, which may lead to under‐reporting of methamphetamine use in the marginalised sub‐population of individuals who use the drug [23]. Efforts to de‐stigmatise methamphetamine use may facilitate more accurate self‐reporting that would provide better prevalence estimates on its use in the population, as well as opportunities for treatment and support to reduce methamphetamine‐related harms for individuals in need.…”
Section: Discussionmentioning
confidence: 99%
“…The survey did not measure if respondents were using other illicit substances concurrently or simultaneously. Our results are based on self-report household surveys in which substance use may be under-reported ( Chan et al., 2022 ). The method of survey administration could impact the prevalence of reported substance use.…”
Section: Discussionmentioning
confidence: 99%